(untitled) (Web of Teachers: Inderscience Research, 2025)
My mother tongue, flowing through our being, stirring in our veins every moment, and influencing our hearts through words. My mother tongue, bringing people closer and widely spreading the seeds of love. As we all know, every nation in this world has its own mother tongue. Language is a part of a nation’s identity. It is not only the pride and honor of the entire people, but also a high distinction. Language is not only a means of communication, but also the culture, customs, lifestyle, and history of a nation.